Bodily interventions and intimate labour : understanding bioprecarity - Griffin, Gabriele; Leibetseder, Doris (Manchester University Press, 2020)
This volume is about the relationship between bodily interventions, intimate labour and bioprecarity. It considers how access to and regulations around different kinds of medical intervention create vulnerabilities, especially for minorities, racialized groups, queers and trans people.